Return to sport after capsuloplasty with a bone block in shoulder instability - Adriano Russo; Augusto Palermo; Luigi Molfetta (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2022)
Objective: Propose a post-surgical rehabilitation program identifying the steps necessary for a progressive recovery of the joint function in compliance with the surgical needs. Material & method: In the anterior and posterior glenohumeral instability, the presence of bone defects, especially at the glenoid side requires surgery and the use of the bone block, associated with the repair of the soft tissues (capsuloplasty). The arthroscopic technique, compared to open surgery, allows respecting  the periarticular anatomical structures, essential for optimal functional recovery. Results: The post-surgical rehabilitation program follows a progressive recovery timing, divided into 3 phases: phase 1 pain control and joint mobility recovery, phase 2 the recovery of strength and specific sport movements and finally phase 3 the return to sports activities. The rehabilitation progress must achieve two objectives: ROM recovery without disturbing the bone graft area, to achieve its integration. Conclusion: the rehabilitation program is ultimately guided by the surgeon considering the strategy adopted in the operating room, the use of the bone-block technique and above all the sealing of the grafts. The physiotherapist following the proposed steps will optimize the final functional result.